2021
DOI: 10.3390/biom11071012
|View full text |Cite
|
Sign up to set email alerts
|

Mitostasis, Calcium and Free Radicals in Health, Aging and Neurodegeneration

Abstract: Mitochondria play key roles in ATP supply, calcium homeostasis, redox balance control and apoptosis, which in neurons are fundamental for neurotransmission and to allow synaptic plasticity. Their functional integrity is maintained by mitostasis, a process that involves mitochondrial transport, anchoring, fusion and fission processes regulated by different signaling pathways but mainly by the peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α). PGC-1α also favors Ca2+ homeostasis, reduces oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 371 publications
(411 reference statements)
1
26
0
Order By: Relevance
“…Our findings provide a plausible framework for the etiology of retinal degeneration by incorporating unique photoreceptor 'omics' and physiology in concert with our observations from the rd1 mutant retina. In addition, our studies are consistent with the mechanistic underpinning of neurodegenerative diseases 62,63 and should have broad implications for deciphering molecular and cellular drivers of disease pathology. Discovery of metabolic and signaling pathways that are altered in anticipation of disease sets the foundation for drug discovery and interventions at an early stage, thereby improving outcomes in clinical management.…”
supporting
confidence: 79%
“…Our findings provide a plausible framework for the etiology of retinal degeneration by incorporating unique photoreceptor 'omics' and physiology in concert with our observations from the rd1 mutant retina. In addition, our studies are consistent with the mechanistic underpinning of neurodegenerative diseases 62,63 and should have broad implications for deciphering molecular and cellular drivers of disease pathology. Discovery of metabolic and signaling pathways that are altered in anticipation of disease sets the foundation for drug discovery and interventions at an early stage, thereby improving outcomes in clinical management.…”
supporting
confidence: 79%
“…Numerous studies highlight the important role of VGCC blockers to treat glutamate excitotoxicity (Godoy et al, 2021;Higley & Sabatini, 2012;Kim et al, 2016;Zyśk et al, 2018). In the light of the results summarized in the literature, N-type blockers are known to have protective effects toxicity of NMDAR-mediated Ca 2+ entry (Kimura et al, 1999;Vallazza-Deschamps et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ homeostasis is essential for the survival of neurons, on the other hand increased intracellular Ca 2+ concentration disrupts calcium homeostasis, and free oxygen radicals formation which could degenerate neurons and synaptic loss (Godoy et al, 2021) (5). For this reason, blocking excitotoxicity through inhibition of VGCC activity in neurons are an especially appealing point for neuroprotection (Godoy et al, 2021;Higley & Sabatini, 2012;Kim et al, 2016). By contrast to neuroprotective effects of P/Q-type and N-type calcium channel blockers, there is a gap for L-type calcium channels blockers in relation to glutamate excitotoxicity (Vallazza-Deschamps et al, 2005;Wheeler et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the decline in brain metabolic activity during aging is associated with mitochondrial dysfunction. Disorders of OXPHOS, imbalanced Ca 2+ buffering, and dysregulation of UPR mt -related proteins lead to neuronal decline during aging [ 71 ]. Under ER stress, Ca 2+ is transported to mitochondria through the MAM, which ultimately leads to increased expression of the mitochondrial protease LONP1 [ 72 , 73 ].…”
Section: Relationships Between Ca 2+ Regulation Mi...mentioning
confidence: 99%